Expression of matrix metalloproteinases, type IV collagen, and interleukin-10 in rabbits treated with morphine after lamellar keratectomy - Ribeiro, Alexandre P.; Silva, Miguel L. [UNESP]; Araujo, Rodrigo L.; Ferrucci, Danilo L.; Mineo, Tiago; Thiesen, Roberto; Bandarra, Marcio de Barros [UNESP]; Laus, Jose L. [UNESP] (Wiley-Blackwell, 2012)
Purpose To study the effects of topical administration of 1% morphine on corneal analgesia in rabbits submitted to lamellar keratectomy and to assess the expression of matrix metalloproteinase-1, metalloproteinase-2, metalloproteinase-9 (MMPs), type IV collagen, and interleukin-10 (IL-10) during the treatment. Methods Morphine group (MG) received 50 mu L of topical 1% morphine four times daily, while the control group received saline instead. Corneal touch threshold (CTT) and the wound area were assessed until corneal healing. Corneal samples were processed for routine histology, immunohistochemistry, zymography, and ELISA. Results Following keratectomy, CTT increased significantly from 6 to 96 h time points. Mean corneal re-epithelization rate and scores of leukocyte infiltration did not differ significantly between treatment groups. Immunolabeling pattern for MMP-1, MMP-9, and type IV collagen was similar in both treatment groups. In the MG, zymography indicated significantly higher levels of active MMP-2 on days 6 and 12; and in the latent MMP-9, on days 3 and 6, and in the active MMP-9, on day 6. Latent MMP-2 and MMP-9, and active MMP-9 decreased to values close to those of healthy corneas on day 12, but levels of active MMP-2 remained significantly elevated in the MG. IL-10 levels measured on days 16 were reduced as compared to those of healthy corneal tissue and returned to levels close to those of healthy corneas on day 12. Conclusion Topical morphine promoted corneal analgesia for up to 4 days and did not delay corneal re-epithelization. The re-establishment of MMPs and IL-10 to levels close to baseline values at the end of the study and the expression of type IV collagen in both groups reinforce that, with caution, 1% morphine can be used after lamellar keratectomy in rabbits.
Keywords: Corneal wound healing; Inflammation; opioids; Pain; Rabbits; side effects